The Effect of Computer-Based Image Series Media toward Description Writing Skills of a Student with Intellectual Dissability in the Grade VII SMPLB - Fenty Ayu Prastikawati; Abdul Huda (Journal of ICSAR, 2018)
One of obstacles faced by them is writing descriptive text. One way to improve descriptive writing skills for a student with intellectual dissability is the use of computer-based image series media. The purpose of this study was to writing skills of a student with intellectual dissability before and after using the computer-based image series media, and to describe the effect of the use of those media towards description writing skills of a student with intellectual dissability. This study used an experimental research with quasi experimental design. The result showed that students’ descriptive writing after used computer-based image series media shows an increasing